Designing Selection Criteria for Use of Reed Canarygrass as a Bioenergy Feedstock. Issue 5 (1st September 2015) - Casler, Michael D.; Cherney, Jerome H.; Charles Brummer, E.; Dien, Bruce S.
ABSTRACT: Reed canarygrass ( Phalaris arundinacea L.) is a perennial C3 grass with a circumglobal distribution in the Northern Hemisphere and adaptation to a wide range of environmental conditions. This species is currently under development as a bioenergy feedstock in North America and Europe. Thus, the objectives of this study were to (i) quantify genetic variation for biomass quality traits of reed canarygrass cultivars and accessions, (ii) determine the relationships for biomass yield with reed canarygrass quality traits, and (iii) identify favorable and attainable breeding objectives for biomass yield and quality traits of reed canarygrass. Eighty cultivars or accessions were grown at five field locations and evaluated for 26 biomass quality traits in 2006 through 2008. Ignoring biomass quality traits in favor of the singular breeding objective of high biomass yield would be likely to result in a few favorable correlated responses including low N, low ash, low Cl, low Fe, and high enzymatic xylan conversion efficiency. These changes would not be sufficiently large to transform reed canarygrass into a more favorable bioenergy feedstock within a few generations of breeding. To do so will require a more focused effort with a relatively small number of traits, for example, high biomass yield, low ash, and high gross calorific value (GCV) for a thermochemical conversion platform or high biomass yield, low lignin, and high glucan and xylan conversion efficiencies for a fermentation platform.